Glicerinas bruta e semipurificada na alimentação de codornas de corte - Farrapo, Samily de Paulo (2015)
The objective was to evaluate the use of mixed and gross glycerines on slaughter quail. Two experiments were performed, one of digestibility to determine the energy values of crude vegetable glycerin and semipurified mixed. The second experiment evaluated the performance, carcass characteristics and meat quail meat receiving different levels of inclusion in the diets of these glycerides. In the digestibility assay was used 180 quails, from 14 to 21 of age, housed in cages for metabolic studies, distributed in a completely randomized design in a factorial 2x2 + 1, 2 ration of replacement reference levels for glycerin (10 and 20%), two types of glycerides (crop and mixed), the more the reference diet, totaling five treatments with 6 replications of 6 birds. The experiment lasted eight days, four for adaptation and four for excreta collection. Gross vegetable glycerin had a higher apparent metabolizable energy corrected by nitrogen balance based on MS (AMEn kcal / kgMS) as the MN (AMEn kcal / kgMN), 5,195 and 4,759, against 3,884 and 3,472 for the semipurified mixed glycerin to the energy values, respectively. In the second experiment we used 432 quails 1- 42 days old, distributed in a completely randomized design in a factorial 2x4 + 1, 2 types of glycerides (vegetable and mixed), 4 glycerines inclusion levels in diets (5, 10, 15 and 20%) over control diet without the addition of glycerin, a total of 9 treatment with 4 replications of 12 birds. At 42 days the birds have undergone solid fasting for eight hours for slaughter, two birds of each separate repetition within the medium weight, for further analysis. It were evaluate the feed intake, weight gain, feed conversion, carcass yield, cuts (breast and thigh + drumstick), abdominal fat, biometry of the organs (liver, heart and gizzard), volatile ammonia, moisture and PH of the bed, as well as physical and sensory characteristics of meat. Data were subjected to analysis of variance and levels of inclusion of glycerides, they were deployed in polynomials. For comparison compared to the control treatment was performed using the Dunnett's test (5%). Difference was observed for performance, where the mixed glycerol provided greater results for feed intake in all periods analyzed, as well as feed conversion 1-21 days and 1-42 days of age of quail. No difference was observed between the glycerides used for volatile ammonia, while between the levels of inclusion of glycerines there was increasing linear effect for this variable as they added either glycerines in feed. The pH was superior to the bed using any inclusion level of vegetable glycerin compared to the control treatment and from 10% to include the pH values are higher when using the vegetable glycerine and not mixed. None of the analyzed factors interfered with the moisture content of the bed. There were no difference for yield, since abdominal fat was higher in birds fed diet containing vegetable glycerin. For the physical characteristics of the meat considered the weight loss for cooking, shear strength and water holding capacity, where data for inclusion levels of glycerides were deployed in polynomials, while for the glycerides used Test F . As for the sensory characteristics, aroma, color, flavor and overall evaluation, the means were compared by 5% Duncan test. The use of vegetable glycerin mixed or no effect on the sensory characteristics of quail meat (P>0.05), can be used in up to 20% inclusion in diets. For the physical difference (P <0.05) for strength and shear levels being 12.5% of GMS and 12.78% of GVB apesentaram that the best results. CRA for PPC and there was no difference (P> 0.05) between treatments analyzed. It follows that the two glycerides have potential to be used up to 20% in the feed quail, without harming the weight gain, the yield and quality of the bed, and the crude glycerin presents the highest amount of energy. However, 13% inclusion of glycerin in quail rations provides a more succulent meat.